2022
DOI: 10.1001/jama.2022.4790
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence of Cigarette Smoking Among US Adults With Major Depression or Substance Use Disorders, 2006-2019

Abstract: IMPORTANCE Tobacco use is highly concentrated in persons with mental illness.OBJECTIVES To assess trends in past-month prevalence of cigarette smoking among adults with vs without past-year depression, substance use disorders (SUDs), or both, using nationally representative data. DESIGN, SETTING, AND PARTICIPANTS Exploratory, serial, cross-sectional study based on data from 558 960 individuals aged 18 years or older who participated in the 2006-2019 US National Surveys on Drug Use and Health. EXPOSURE Past-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 31 publications
3
53
0
1
Order By: Relevance
“…The prevalence of smoking in the United States has fallen dramatically over the past 50 years, from 42 to 14% of the adult population [1]. Meanwhile, prevalence among individuals with mental health and substance use disorders (MH/SUD) has shown more limited reduction [2–4]. Risk ratios for smoking are 2.1 for any current psychiatric diagnosis; between 2 and 3 for many common individual diagnoses including depression, anxiety and alcohol use disorder; and greater than 3 for dual disorders and drug use disorders [5–7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of smoking in the United States has fallen dramatically over the past 50 years, from 42 to 14% of the adult population [1]. Meanwhile, prevalence among individuals with mental health and substance use disorders (MH/SUD) has shown more limited reduction [2–4]. Risk ratios for smoking are 2.1 for any current psychiatric diagnosis; between 2 and 3 for many common individual diagnoses including depression, anxiety and alcohol use disorder; and greater than 3 for dual disorders and drug use disorders [5–7].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the potential role of health insurance expansion in improving tobacco‐related health outcomes among underserved populations, including lower income adults and those with MH/SUD. Although nationally representative trends in smoking for adults with MH/SUD have declined since the passage of the ACA [4], little has been reported about how insurance coverage changes have been associated with changes in smoking rates among adults with MH/SUD.…”
Section: Introductionmentioning
confidence: 99%
“…From 2006 to 2019, the difference in past-month prevalence of cigarette smoking between individuals with and without MDE declined significantly from 11.5% to 6.6%. 1 Prior studies [2][3][4] have not demonstrated declines in pastmonth prevalence of cigarette smoking in individuals with SUD and other mental illnesses, highlighting the novelty of our findings. 1 Furthermore, among adults with MDE and/or SUD, our results showed that the lifetime prevalence of cigarette smoking did not decline as much as past-month prevalence, indicating that the reductions in past-month smoking were due to quitting at some time after onset of smoking.…”
mentioning
confidence: 50%
“…Thus, tobacco cessation explains the relative improvements in pastmonth prevalence of cigarette smoking. 1 Our study 1 demonstrates that progress has been made by public health tobacco control measures and prevention intervention efforts for adults in the US, including those with MDE or SUD. However, higher past-month prevalence of smoking persists among adults with MDE or SUD, highlighting the ongoing need for smoking cessation efforts that target these individuals.…”
mentioning
confidence: 73%
See 1 more Smart Citation